Intestinal ills - Jamison, Alcinous B. (Alcinous Burton), 1851-1938 (Salt Lake City, UT : Project Gutenberg, 2008)
"Intestinal Ills" by Alcinous B. Jamison is a scientific publication written in the early 20th century. The book addresses various gastrointestinal disorders, particularly chronic constipation, and discusses underlying causes such as proctitis and colitis, as well as their effects on overall health. The text emphasizes the importance of intestinal cleanliness and aims to provide both knowledge and remedies for common ailments affecting the digestive system. The opening of the work introduces the author$1 (Bs perspective on the common health issues linked to improper bowel function, such as chronic constipation and its symptoms, which range from indigestion to auto-intoxication. Jamison outlines how neglect of intestinal health leads to systemic infections and emphasizes that many diseases could potentially be traced back to issues within the lower bowels. The chapter sets the tone for a thorough exploration of the interdependence between various digestive functions, the impact of food intake on gut health, and the critical need for consistent and effective bowel function. (This is an automatically generated summary.)s
Release date is 2008-08-19
E-text prepared by Juliet Sutherland and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Intestines -- Diseases; Rectum -- Diseases; Constipation; Gastroenterology